A DEVICE FOR PRODUCING HYDROGEN BY CHEMICAL MEANS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The search for alternative sources of energy and fuel is a very important social problem today. Hydrogen, currently, is considered as a promising energy carrier, which is able to provide possible, simpler, environmentally friendly energy, its production volumes are rapidly growing and after a while will replace hydrocarbon fuels—oil, gas, coal. The transition to hydrogen energy plays a dominant role in the fight for climate conservation, and hydrogen produced from water is also an ideal fuel of the future, since Kyrgyzstan has a huge water potential. The article presents a hydrogen production device and experimental results of hydrogen production based on a chemical method. It is shown that when hydrogen is produced by chemical means, sodium aluminate is formed, and it is in demand in the industry when aluminum is produced. Sodium aluminate during the preliminary processing of aluminum ore takes its initial state, that is, a circular cycle occurs.
Keywords: hydrogen energy, energy efficiency, waste-free, circular cycle